Cooled-radiofrequency neurotomy for the treatment of chronic lumbar facet (zygapophyseal) joint pain: A retrospective study. Issue 52 (30th December 2021) - Candan, Burcu; Gungor, Semih
Abstract : Abstract: Cooled-radiofrequency (CRFA) is a newer technique and may have some theoretical advantages over traditional radiofrequency ablation (TRFA). In this study, we aimed to investigate the efficacy and safety of CRFA for the treatment of lumbar facet joint-mediated pain. In this retrospective study, we evaluated 185 CRFA performed on 105 patients. All patients with axial lower back who received the preliminary diagnosis of lumbar facet joint-mediated pain and refractory to conservative therapy underwent diagnostic medial branch blocks. CRFA was recommended to those patients who responded favorably to two sets of diagnostic medial branch blocks. Pain scores in numeric rating scale (NRS) were recorded pre-treatment and post-treatment at different time-points. The primary outcome measure was to report descriptive NRS score and average % improvement from baseline at each time point. A significant pain relief was determined by a decrease of ≥50% of mean NRS. Secondary outcome measure was the time to repeat treatment with subsequent CRFA. Adverse events were also recorded. Primary outcome measure determined as the improvement in NRS, for at least 50% or more, was achieved in both 1st (4–8 weeks) and 2nd (>2–6 months) follow-up (FU) with 60.5% and 53.6% reduction in NRS respectively. Our subgroup analysis comparing the younger (<50) and older (≥50) age groups showed superior pain relief with CRFA in the older (≥50) age group, both in the 1st (4–8 weeks) and 2nd (>2–6 months) FU time points (63.4% and 58.4% reduction in NRS, respectively). Cooled-radiofrequency ablation is an effective and safe procedure for the treatment of chronic lumbar facet joint related pain. The duration of pain relief was comparable to traditional radiofrequency ablation as reported in the literature.